A Phase I-II Evaluation of Veliparib (NSC #737664), Topotecan, and Filgrastim or Pegfilgrastim in the Treatment of Persistent or Recurrent Carcinoma of the Uterine Cervix: An NRG Oncology/Gynecologic Oncology Group Study. Issue 3 (1st March 2015) - Kunos, Charles; Deng, Wei; Dawson, Dawn; Lea, Jayanthi S.; Zanotti, Kristine M.; Gray, Heidi J.; Bender, David P.; Guaglianone, Perry P.; Carter, Jori S.; Moore, Kathleen N.
Abstract : Purpose: The aim of this study was to evaluate the tolerability and efficacy of poly(ADP-ribose) polymerase (PARP) inhibition by veliparib during cytotoxic topotecan administration with filgrastim or pegfilgrastim neutrophil support in women with persistent or recurrent uterine cervix cancer. Experimental Design: This phase I-II trial examined twice-daily oral veliparib (10 mg) given during once-daily intravenous topotecan (0.6 mg/m 2 ) on days 1 to 5 of each treatment cycle. Cycles were repeated every 21 days until disease progression or until toxicity prohibited further therapy. Toxicity and objective response rate were primary endpoints. Results: Twenty-seven women were enrolled. Frequently reported grade 3 or higher treatment-related toxicities were anemia (59%), thrombocytopenia (44%), leukopenia (22%), and neutropenia (19%). There were 2 partial responses (7% [90% confidence interval, 1%–22%]). Four patients had a disease progression date more than 6 months after the start of veliparib-topotecan therapy. Patients with low immunohistochemical expression (0–1+) of PARP-1 in their primary uterine cervix cancer were more likely to have a longer progression-free interval (hazard ratio, 0.25; P = 0.02) and survival (hazard ratio, 0.12; P = 0.005) after veliparib-topotecan therapy. Conclusions: Clinical activity of a veliparib-topotecan combination was minimal in women with persistent or recurrent uterine cervix cancer. Women whose uterine cervix cancers express PARP-1 at low levels may benefit preferentially from PARP inhibitors combined with cytotoxic therapies, suggesting further study of PARP expression as an integral triage biomarker.